Pendant allyl crosslinking as a tunable shape memory actuator for vascular applications. (15th September 2015) - Boire, Timothy C.; Gupta, Mukesh K.; Zachman, Angela L.; Lee, Sue Hyun; Balikov, Daniel A.; Kim, Kwangho; Bellan, Leon M.; Sung, Hak-Joon
Graphical abstract: Abstract: Thermo-responsive shape memory polymers (SMPs) can be programmed to fit into small-bore incisions and recover their functional shape upon deployment in the body. This property is of significant interest for developing the next generation of minimally-invasive medical devices. To be used in such applications, SMPs should exhibit adequate mechanical strengths that minimize adverse compliance mismatch-induced host responses (e.g. thrombosis, hyperplasia), be biodegradable, and demonstrate switch-like shape recovery near body temperature with favorable biocompatibility. Combinatorial approaches are essential in optimizing SMP material properties for a particular application. In this study, a new class of thermo-responsive SMPs with pendant, photocrosslinkable allyl groups, x %poly(ε-caprolactone)-co- y %(α-allyl carboxylate ε-caprolactone) ( x %PCL- y %ACPCL), are created in a robust, facile manner with readily tunable material properties. Thermomechanical and shape memory properties can be drastically altered through subtle changes in allyl composition. Molecular weight and gel content can also be altered in this combinatorial format to fine-tune material properties. Materials exhibit highly elastic, switch-like shape recovery near 37 °C. Endothelial compatibility is comparable to tissue culture polystyrene (TCPS) and 100%PCL in vitro and vascular compatibility is demonstrated in vivo in a murine model of hindlimb ischemia, indicating promising suitability for vascular applications. Statement of Significance: With the ongoing thrust to make surgeries minimally-invasive, it is prudent to develop new biomaterials that are highly compatible and effective in this workflow. Thermo-responsive shape memory polymers (SMPs) have great potential for minimally-invasive applications because SMP medical devices (e.g. stents, grafts) can fit into small-bore minimally-invasive surgical devices and recover their functional shape when deployed in the body. To realize their potential, it is imperative to devise combinatorial approaches that enable optimization of mechanical, SM, and cellular responses for a particular application. In this study, a new class of thermo-responsive SMPs is created in a robust, facile manner with readily tunable material properties. Materials exhibit excellent, switch-like shape recovery near body temperature and promising biocompatibility for minimally-invasive vascular applications.